Antioxidant Activity Test of Titanus (Leea aequata L) Leaf Extract with DPPH Method - Sihotang, Nurhanifah; Bangar, Roy Indrianto; Kaban, Vera Estefania; Br Sembiring, Novitaria; Harahap, Daimah Wirdatus Sanaun (CV. Nusantara Scientific Medical, 2025)
Free radicals play an important role in oxidative stress, which can lead to a number of degenerative diseases, including heart disease, cancer and premature aging. Natural and artificial ingredients can be used to make antioxidants. The use of synthetic antioxidants is starting to be limited because excessive use can cause negative side effects, such as the accumulation of toxins in the body. This study aims to evaluate the antioxidant activity of tetanus (Leea aequata L.) leaf extract using DPPH method. Free radicals generated during metabolism can cause cell damage and contribute to various degenerative diseases. Therefore, it is important to find effective sources of antioxidants. In this study, Tetanus leaves were extracted using 96% ethanol solvent through maceration method. Antioxidant activity was evaluated by measuring the IC50 value against DPPH radical. The results showed that tetanus leaf extract had an IC50 value of 39.484 ppm, which indicated significant antioxidant activity. These results indicate that tetanus leaf extract can function as a free radical scavenging agent, which could potentially serve as a raw material in the development of herbal medicine to prevent oxidative stress-related diseases.